Alteration of hippocampal parvalbumin interneurons underlies memory impairment in rat model of Parkinson's disease - Radovanovic, Ljiljana; Saponjic, Jasna; Petrovic, Jelena (Frontiers in Behavioral Neuroscience, 2026)
Cognitive decline is a major non-motor symptom in patients with Parkinson's disease (PD) that can be present as early as the prodromal stage. As a multisystem neurodegenerative syndrome, PD is associated with disturbances in various neurotransmitters, including dopamine, acetylcholine, serotonin, noradrenaline, glutamate, and gamma-aminobutyric acid (GABA). While the roles of dopaminergic and cholinergic deficiencies in cognitive impairment in PD are well documented, the contribution of the GABAergic system is less clear. We investigated spatial and recognition memory, along with changes in hippocampal GABAergic parvalbumin-positive (PV+) neurons, in distinct rat models of PD neuropathology. PD cholinopathy was induced by bilateral pedunculopontine tegmental nucleus (PPT) lesion, hemiparkinsonism was induced by unilateral substantia nigra pars compacta (SNpc) lesion, and hemiparkinsonism with PD cholinopathy was induced by unilateral SNpc and bilateral PPT lesions. Behavioral tests were conducted 14 and 42 days after lesions and included assessments of spatial memory (spatial habituation test), recognition memory (novel object recognition test), and measurements of motor activity (open field test). Motor function was preserved in all PD models. We observed delayed impairments in spatial and recognition memory in PD cholinopathy, and persistent impairment in spatial memory in hemiparkinsonism, although hippocampal PV expression remained unchanged over time. In hemiparkinsonism with PD cholinopathy, persistent spatial memory impairment was followed by delayed recognition memory deficits, along with hippocampal PV suppression, which was functionally linked to recognition memory impairment. Our results show that different PD neuropathologies underlie different memory impairments in rats. While dopaminergic denervation plays an important role in impairing spatial memory from the prodromal stage of PD, cholinergic denervation impairs recognition memory in a delayed manner. However, only their synergistic dysfunction alters hippocampal GABAergic PV+ neuron-mediated inhibitory transmission during PD progression, which was correlated with memory impairment.